Multi-Carrier based 27-level Hybrid Multi-level Inverter Interface with PhotoVoltaic - P. Kiruthika; Ramani Kannan (Institute of Advanced Engineering and Science, 2015)
This paper presents a Multi-Carrier Pulse Width Modulation control for a Single-phase 27-level Hybrid Multi-Level Inverter for photovoltaic systems. Multi-Carier Pulse Width Modulation technique uses a easy mapping to generate gate signals for the inverter.The Maximum Power Point Tracking is capable of extracting maximum power from PV array connected to each DC linkage voltage stage. The Maximum Power Point Tracking algorithm is solved by Perturb and Observer method.This is done to accomplish high energetic performance with low Total Harmonic Distortion.The grades are compared with conventional Multi-Level Inverter in terms of inferior THD is obtained and the 27-level Hybrid Muti-Level Inverter is simulated by using MATLAB/simulink.Simulated results are available to verify the usefulness and accuracy of the proposed method. This proposal can be easily extended to an n-level inverter for PV system. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7140